A Monte-Carlo method for interface dosimetry of beta emitters. - Buffa, F; Verhaegen, F; Flux, G; Dearnaley, D (2003)
Biologically targeted radiotherapy optimization requires accurate dose estimation, from macroscopic to cellular/subcellular dimensions. In particular, dose perturbations produced at interfaces between dissimilar media could affect therapy outcome. The magnitude of these perturbations depends on a complex set of parameters. This study investigates perturbations on electron dose for materials with atomic numbers (Z) up to 79 (79Au) at their interface with water as a function of Z, energy, distance from interface and geometry. A Monte-Carlo method that produces absorbed dose distributions in a voxel geometry has been developed using EGSnrc transport routines. Heterogeneous media and activity distributions can be input into this code. The backscatter dose factor (BSDF), which quantifies interface dose perturbations, was estimated using this code. The BSDF magnitude ranged from approximately 3% to approximately 50%, depending on source energy and Z. The BSDF decreased with increasing energy and showed a logarithmic dependence on Z. Empirical functions were fit to the results, that could be used to correct dose calculations performed using dose-point-kernels estimated in water, to cases involving different scattering materials. The BSDF was found to be highly dependent on interface geometry and scoring volume; thus it is vital that BSDFs are used only in geometry conditions that are similar to those in which they were originally produced.